Quasisynchronization in Quorum Sensing Systems with Parameter Mismatches. (16th July 2014) - Zhang, Jianbao; Zhang, Wenyin; Ma, Zhongjun; Yu, Jing
Abstract : The paper investigates quasisynchronization in a communication system, which consists of cells communicating through quorum sensing. With the help of Lyapunov function method and Lur'e system approach, some sufficient conditions for quasisynchronization are presented, and a bound on the synchronization errors is derived. The obtained theoretical results show that the synchronization quality is influenced by two parameters detrimentally: the error bound depends almost linearly on the mismatches between cells and depends sensitively on the diffusion rates of the signals inward the cell membrane. Numerical experiments are carried out to verify the theoretical results.